2015
DOI: 10.1007/s12035-014-9089-7
|View full text |Cite
|
Sign up to set email alerts
|

Adult Deletion of SRF Increases Epileptogenesis and Decreases Activity-Induced Gene Expression

Abstract: Although the transcription factor serum response factor (SRF) has been suggested to play a role in activity-dependent gene expression and mediate plasticity-associated structural changes in the hippocampus, no unequivocal evidence has been provided for its role in brain pathology, such as epilepsy. A genome-wide program of activity-induced genes that are regulated by SRF also remains unknown. In the present study, we show that the inducible and conditional deletion of SRF in the adult mouse hippocampus increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 85 publications
9
60
1
Order By: Relevance
“…2c, bottom; Additional file 1: Figure S1, bottom) also revealed that previous several experimental data had similar comprehensive gene expression to GSE62385 (IHT or aging) as follows: aging (18 months old vs. 3.5 months old) (GSE29075) [32], kainic acid (KA) treatment (KA-treated mice vs. Saline-treated mice) (GSE60772) [33], Dicer ablation (Dicer knock out (KO) mice vs. Ctrl) (GSE23847, GSE61937) [34, 35], and moderate glutamate excess (glutamate dehydrogenase 1 (Glud1) transgenic (Tg) mice vs. Ctrl) (GSE11419) [36, 37]. In particular, the alteration patterns of clusters A, B, C and E in these experimental models are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 70%
“…2c, bottom; Additional file 1: Figure S1, bottom) also revealed that previous several experimental data had similar comprehensive gene expression to GSE62385 (IHT or aging) as follows: aging (18 months old vs. 3.5 months old) (GSE29075) [32], kainic acid (KA) treatment (KA-treated mice vs. Saline-treated mice) (GSE60772) [33], Dicer ablation (Dicer knock out (KO) mice vs. Ctrl) (GSE23847, GSE61937) [34, 35], and moderate glutamate excess (glutamate dehydrogenase 1 (Glud1) transgenic (Tg) mice vs. Ctrl) (GSE11419) [36, 37]. In particular, the alteration patterns of clusters A, B, C and E in these experimental models are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 70%
“…The mitogen-activated protein kinase (MAPK) and phosphatidylinositol-3 kinase (PI3K) pathways have been shown to be required for the induction of Npas4 by pharmacologically-induced LTP (long term potentiation) and LTD (long term depression), respectively, in mouse hippocampal slices [15]. A recent study showed that serum response factor (SRF) is a possible upstream regulator of Npas4, as its deletion led to a significant decrease in Npas4 expression [16]. Npas4’s promoter region contains two SRF binding sites, suggesting that SRF directly regulates Npas4 expression.…”
Section: Activity-dependent Induction Of Npas4mentioning
confidence: 99%
“…In a previous study, enhanced SRF occupancy at target genes was reported in the rat pilocarpine model [22]. However, so far, an impact of SRF on gene expression, seizure occurrence and histo-pathological seizure hallmarks was not investigated in the pilocarpine model.…”
Section: Introductionmentioning
confidence: 99%